2021
DOI: 10.2196/26162
|View full text |Cite
|
Sign up to set email alerts
|

Patient Perceptions on Data Sharing and Applying Artificial Intelligence to Health Care Data: Cross-sectional Survey

Abstract: Background Considerable research is being conducted as to how artificial intelligence (AI) can be effectively applied to health care. However, for the successful implementation of AI, large amounts of health data are required for training and testing algorithms. As such, there is a need to understand the perspectives and viewpoints of patients regarding the use of their health data in AI research. Objective We surveyed a large sample of patients for identifying current … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 27 publications
(34 reference statements)
3
33
0
Order By: Relevance
“…The big majority only knew ‘somehow’ what it meant or even less, which was in a similar range already shown for the German as well as other populations. 21 , 62…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The big majority only knew ‘somehow’ what it meant or even less, which was in a similar range already shown for the German as well as other populations. 21 , 62…”
Section: Discussionmentioning
confidence: 99%
“…Aggarwal and colleagues examined perceptions of 408 participants from London regarding AI along with questions about data collection and data sharing for the purpose of medical AI research. 21 They found that while patients generally have little prior knowledge about AI, the majority perceives its usage as positive, trusts its use and believes that the benefits outweigh the risks. A common finding in many studies is that patients want physician supervision of AI and prefer a physician in a direct comparison.…”
Section: Introductionmentioning
confidence: 99%
“…AI-research has focused on studies investigating accuracy of AI-based systems, while there is a gap in knowledge on patients' and physicians' perspectives towards AI. Successful implementation of AI into routine clinical practice depends not only on technical challenges, but also on the public's trust and acceptance of AI 14 . Trust in AI is determined by the way people interact with the technology and dependent on the ease of use, reliability, transparency, explainability, security and privacy protection, and communication on the use of AI systems 13 .…”
Section: Discussionmentioning
confidence: 99%
“…The fast evolutions and developments in AI may result in an overflow of information, unmanageable for patients and physicians. This may paradoxically discourage further developments and implementation, emphasizing the importance of education and training 14,17 .…”
Section: Discussionmentioning
confidence: 99%
“…Although studies have been conducted to gauge patient [21][22][23][24] and researcher [25] sentiments on sharing clinical data, there is limited information on practitioner perception [26][27][28][29][30] to sharing patient information. Understanding practitioner perception is critical, as in most countries, practitioners are the custodians of their patient's data and have ultimate decision as to its use.…”
Section: Introductionmentioning
confidence: 99%